Natural Inhibitors for Corrosion Protection of 6061 Aluminum Alloy: A Review - Maulana Witanta; I Gusti Ayu Arwati; Edy Herianto Majlan (International Journal of Innovation in Mechanical Engineering and Advanced Materials, 2025)
6061 aluminum alloys are widely used in automotive, marine, and aerospace industries, yet their high susceptibility to corrosion in acidic and chloride environments remains a challenge. Bio-based inhibitors from natural sources have emerged as sustainable alternatives to toxic synthetic chemicals. This review synthesizes findings from published studies on AA6061 alloys and composites, integrating evidence from Potentiodynamic Polarization (PDP), Electrochemical Impedance Spectroscopy (EIS), and Scanning Electron Microscopy (SEM). Cross-study evaluations show that inhibition efficiency depends on inhibitor type and mechanism. Reports indicate that Boswellia serrata provides only moderate protection (~70%) due to weak physiosorbed films that are unstable under flow, whereas Alocasia odora achieves higher efficiency (~94% in HCl) through chemisorption with cathodic inhibition. Aerva lanata demonstrates ~88% efficiency in chloride-based fiber-metal laminates via polyphenolic adsorption, while glutathione provides ~80% protection at 0.75 mM through multisite coordination. Pectin consistently achieves the highest efficiency (~95% in mild acidic media) by forming compact polymeric films that increase charge-transfer resistance and reduce double-layer capacitance. This synthesis indicates that chemisorption-based inhibitors (e.g., pectin, Alocasia) generally outperform physisorption-based systems (e.g., Boswellia) because they form stronger and more stable films. Reported studies highlight both advantages and limitations: natural inhibitors are effective and eco-friendly, but most evaluations remain short-term and laboratory-based. Key gaps include durability testing, advanced characterization (XPS, ToF-SIMS, Raman, AFM), galvanic effects in composites, and poor hydrodynamic stability of physisorption systems. Future work should explore hybrid strategies, synergistic multi-inhibitor approaches, and validation under real-sea conditions to enable scalable and industrially viable corrosion protection.